Nie trwam o jedzę, kiedy dobrze siedzę. O jedzeniu i żarciu w paremiologii polskiej dawnej i współczesnej - Skorupska-Raczyńska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The analysis of 694 proverbs selected from widely accessible collections allows their classification into semantic fields ranging from names of foods, ways of eating, the necessity and urge to eat as well as the effects of eating, to the rules of eating and conduct during meals. Most of the proverbs analysed refer to actual situations (ca. 84%); the remaining (ca. 16%) include metaphors that illustrate or codify social behaviours and their consequences. Proverbs registered in the 19th century written Polish language constitute over a half (52,4%) of the data, while those from the 20th century amount to over one fourth (26,3%). The rest (26,3%) is dated as coming from the 15th–18th century. Over 72% of the proverbs analysed are syntactically complex with regular sound instrumentation and about 28% are syntactically simple. The analysis brings out a very important need to regulate the rules of the eating process and of conduct while eating, as well as the significance of healthy nutrition.